Energy metabolism and body composition in athletes - Sagayama, H. (Japanese Journal of Physical Fitness and Sports Medicine, 2018)
In this review, the energy metabolism and body composition in athletes are discussed on the basis of an energy balance study using a doubly labeled water method. In athletes, the energy expenditure induced by sports activities widely differs according to the type of sports event. In addition, the physical activity of athletes can reach more than twice the basal metabolic rate throughout the sports season. It may be also more than three times depending on the duration of the tournament and/or the training camp. Thus, the event type, and training time and intensity must be considered when estimating the energy requirement of athletes.